IMPLEMENTASI ETOS KERJA GURU PJOK DI ERA SOCIETY 5.0 - Nanda Aghni Ridwan; Muhibuddin Fadli; Nanda Aghni Ridwan (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Abstract: This research is motivated by the implementation of the work ethic of secondaryschool teachers in the era of society 5.0, one of which is discipline. Discipline is acrucial part of learning, where without awareness of following the rules that havebeen set, the learning process will not achieve the desired goals. In the age ofSociety 5.0, PJOK teachers must have the ability to use digital technology to createcreative and innovative learning. This research was carried out through the libraryresearch method. The library research process is carried out by researching relevantliterature and analyzing the combined topics. The importance of developing thecompetence of PJOK Teachers is emphasized, and this must be done throughplanned and sustainable coaching programs to improve the quality of theirprofessionalism. Therefore, continuous improvement in the quality of teachers aslearners and educators must be a priority through planned and sustainableprograms. Striving for a work ethic that prioritizes high-quality service leads us tounderstand that the position itself is simply the position held, while professionalismrefers to the skills or expertise possessed in carrying out a particular position.Professionalism is essentially the essence of a profession and the individual whoholds that professional position